PERANAN GURU IPA DAN IPS DALAM MENANAMKAN NILAI YANG TERKANDUNG DALAM KONTEN IPA DAN IPS DI MADRASAH IBTIDA’IYAH - Nafia Wafiqni; Burhanudin Milama (TARBIYA: Journal of Education in Muslim Society, 2014)
This study aimed at determining the role of science and social studies teachers in instilling the values contained in science and social studies content at Government Elementary School. The method used in this research was descriptive qualitative. Through a case study, this qualitative approach was intended to gain in dept understanding of social situation, and find patterns, hypotheses and theories. Subjects in this study were 10 teachers who teach science and social studies at Islamic elementary schools that were selected from randomly chosen elementary schools from North Jakarta, South Jakarta, Central Jakarta, West Jakarta and East Jakarta. The results of the study revealed  that responsibility, collaborative work, mutual respect, and respect could be developed by teachers through teaching and learning process. Yet, other values that were specifically generated from the material content of science and social studies have not been tried out to be developed except in teachers’ lesson plans. DOI: 10.15408/tjems.v1i2.1271